Adoption of Electronic Personal Health Records in Canada: Perceptions of Stakeholders - Gagnon, Marie-Pierre (Int J Health Policy Manag, 2016)
Background: Healthcare stakeholders have a great interest in the adoption and use of electronic personal health records (ePHRs) because of the potential benefits associated with them. Little is known, however, about the level of adoption of ePHRs in Canada and there is limited evidence concerning their benefits and implications for the healthcare system. This study aimed to describe the current situation of ePHRs in Canada and explore stakeholder perceptions regarding barriers and facilitators to their adoption. Methods: Using a qualitative descriptive study design, we conducted semi-structured phone interviews between October 2013 and February 2014 with 35 individuals from seven Canadian provinces. The participants represented six stakeholder groups (patients, ePHR administrators, healthcare professionals, organizations interested in health technology development, government agencies, and researchers). A detailed summary of each interview was created and thematic analysis was conducted. Results: We observed that there was no consensual definition of ePHR in Canada. Factors that could influence ePHR adoption were related to knowledge (confusion with other electronic medical records [EMRs] and lack of awareness), system design (usability and relevance), user capacities and attitudes (patient health literacy, education and interest, support for professionals), environmental factors (government commitment, targeted populations) and legal and ethical issues (information control and custody, confidentiality, privacy and security). Conclusion: ePHRs are slowly entering the Canadian healthcare landscape but provinces do not seem well-prepared for the implementation of this type of record. Guidance is needed on critical issues regarding ePHRs, such as ePHR definition, data ownership, access to information and interoperability with other electronic health records (EHRs). Better guidance on these issues would provide a greater awareness of ePHRs and inform stakeholders including clinicians, decision-makers, patients and the public. In turn, it may facilitate their adoption in the country